(untitled) (Malaysian Management Journal, 2015)
We examined the influence of the success of Information Technology (IT) on the Quality of Working Life (QWL). We first explored the success dimensions of IT/IS and also dimension of QWL. Then, we proposed a new model – managing IT for improving QWL model - to explain and predict the influence of IT’s success on employees’ QWL. Drawing on the previous literature, and the results of a series of case studies, the managing of IT to improve the QWL model, integrates several sets of factors that are influencing the improvement of QWL: organizational factors; quality of IT; employees’ attitudes to IT; employees’ use of IT; perceived usefulness of IT and QWL. These sets of factors are drawn from well-established frameworks (IS’s implementation, IS’s success and TAM models). Results from a survey involving 299 IT users in semnan province (Iran) indicate that a positive relationship exists between IT’s success and QWL. The analysis provided strong support for the model, with 15 of 17 hypotheses which are supported. Path analysis was also used to test the research model. The study used theoretical and empirical evidence to propose a model and then validate it by using quantitative data from industrial organizations in Semnan. Finally the model was validated by path analysis.